PENGARUH KESELAMATAN DAN KESEHATAN KERJA(K3) DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. YASMINA PILAR UTAMA UNIT KERJA RUMAH SAKIT CIPTO MANGUNKUSUMO JAKARTA PUSAT - Romadan, Dadan; Priadi, Andri (Journal of Research and Publication Innovation, 2024)
This study was to determine the positive and significant effects of occupational safety and health variables on employee performance, to find out the positive and significant effects of work discipline variables on employee performance and to find out the positive and significant effects of work safety and health variables and simultaneous work discipline on employee performance on PT. South Jakarta Main Pillar Yasmina. The sample used was a Slovine sampling technique with a 10% error rate formulated to a total of 83 respondents. The method used is a quantitative descriptive method. Data collection techniques through primary and secondary data Data analysis techniques use descriptive statistics, validity tests, reability tests, normality tests, multicolonierity tests, autocorrelation tests, heterocorrelation tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-test and f-test. Research results show that: (1) there is a partial positive and significant effect between occupational safety and health on employee performance on PT. Yasmina Pilar Utama South Jakarta, this can be proven from the simple linear regression equation Y = 18.349 + 0.547X1 and the thitung value > t table or (5.936 > 1,664). with a significance of 0.000 < 0.050. (2) Partially, there is a positive and significant influence between work disciplines on employee performance on PT. Yasmina Pilar Utama South Jakarta, this can be demonstrated from the simple linear regression equation Y = 12.008 + 0.703X2 and count > t table or (7.188 > 1,664). with a significance of 0.000 < 0.050. (3) simultaneously there is a positive and significant effect between occupational safety and health and work discipline on employee performance on PT. Yasmina Pilar Utama South Jakarta, this can be proven from the multiple linear regression equation Y = 11.445 + 0.142X1 + 0.574X2, correlation value 0.630, coefficient determination value 39.7%, and F count value > F table or 26.316 > 2,720 with significance level 0.000 < 0.050.